Estimating the weighted prevalence of anxiety disorders in breast cancer patients using a Two-stage approach - Fatiregun Olamijulo; Ogunnubi Oluseun Peter; Fatiregun Omolara; Oyatokun Bolutife; Osunwale Dahunsi; Erinfolami Adebayo; Adeyemi Joseph (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: A two-stage survey is useful when the actual diagnostic interview is time-consuming and expensive to administer on the general population. Objective: To compare Schedule for Clinical Assessment in Neuropsychiatry (SCAN) with Hospital Anxiety and Depression Scale (HADS) in the determination of the prevalence of anxiety disorder in patients with breast cancer. Methods: A cross-sectional study of 200 female patients diagnosed with breast cancer attending the Oncology Out-Patients Clinic of the Lagos State University Teaching Hospital, Ikeja, Lagos, Nigeria was done. The instruments used for the survey included a socio-demographic questionnaire, the HADS and the SCAN. Results: The mean age of the subjects was 49.6 ± 11.2 years. Majority of the subjects (76.5%) were married. Using HADS with a threshold score of ≥ 8, 53 (26.5%) met the criteria for probable anxiety disorders (herein called 'cases'). Of the 68 patients (all 53 'cases' plus 15 randomly selected 10% of the non-cases) interviewed with the SCAN instrument, only 38 met the criteria for diagnosis of anxiety disorder. Conclusions: The prevalence of anxiety disorders can be determined with greater precision using the two-stage design approach. Diagnostic tools like SCAN should therefore be incorporated in the assessment protocols for patients with breast cancer and other illnesses.